The impact of breathing amplitude on dose homogeneity in intensity modulated proton therapy. (July 2017) - Protik, Angjelina; van Herk, Marcel; Witte, Marnix; Sonke, Jan-Jakob
Abstract: Background/purpose: Intensity-modulated proton therapy (IMPT) dose distributions can be severely degraded in targets moving with respiration due to the interplay, range and blurring effects. In this study we investigated the joint and disentangled impact of these effects as a function of the motion amplitudes. Materials/methods: Single-fraction time-resolved proton treatment delivery was simulated using an in-house developed 4D-motion simulation platform. The respiratory induced anatomical changes were described by deformation vector fields (DVF) derived from 4D-Computed Tomography (4D-CT) scans scaled to different motion amplitudes. Based on the individual spots exported from IMPT plans for 10 lung cancer patients, three dose distributions with different combinations of motion effects were generated. The doses were subtracted from each other to study the separated impact of individual effects over the planning target volume (PTV). The results were evaluated using univariate and multivariate regression models including amplitude, tumour size and location. Results: The interplay effect led to an average dose error of 7% for motion amplitude of 20 mm, whereas range and blurring effects were smaller at 2.6% and 2.5%, respectively. These effects increased linear-quadratically with amplitude and were significantly associated with tumour volume or location. Conclusion: Single-fraction dose variations due to interplay effects dominate other respiratory-induced variations for a large range of motion amplitudes.